SOFT INTERVAL VALUED INTUITIONISTIC FUZZY SEMI-PRE GENERALIZED CLOSED SETS - Lancy, A. Arokia (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
The purpose of this paper is to introduce some generalized closed sets of general topology to soft interval valued intuitionistic fuzzy topology. In particular the soft interval valued intuitionistic fuzzy semi-pre generalized closed sets along with its characterization are discussed. Keywords: Soft interval valued intuitionistic fuzzy open set (semi-open set, pre-open set, semi-pre open set, Â - open set) soft interval valued intuitionistic semi â€“pre generalized closed set.